2021
DOI: 10.1055/a-1681-1916
|View full text |Cite
|
Sign up to set email alerts
|

When Your Ankle Becomes a Knee – Long-Term Functional Outcome and Quality of Life with a Rotationplasty after Resection of Malignant Limb Tumors

Abstract: Background Increasing numbers of patients surviving malignant bone tumors around the knee joint have led to an increasing importance to investigate long-term results. This study assessed the long-term results of rotationplasty after resection of malignant bone tumors regarding functional outcome and quality of life to allow better comparison with other treatment options in bone cancer treatment. Proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Regarding MSTS, previous studies reported varied results. 2,3,6,8,10-13 Considering that our patient reached a high level of function during POMs 6–12 (i.e., over a relatively short period), it can be inferred that the post-KRP rehabilitation protocol applied is beneficial in improving physical function. Furthermore, TESS gradually improved in response to muscle strength and physical function.…”
Section: Discussionmentioning
confidence: 90%
“…Regarding MSTS, previous studies reported varied results. 2,3,6,8,10-13 Considering that our patient reached a high level of function during POMs 6–12 (i.e., over a relatively short period), it can be inferred that the post-KRP rehabilitation protocol applied is beneficial in improving physical function. Furthermore, TESS gradually improved in response to muscle strength and physical function.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the family was worried about the psychological burden of the unusual appearance of the limb after rotationplasty, although published literature does not support these concerns. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the family was worried about the psychological burden of the unusual appearance of the limb after rotationplasty, although published literature does not support these concerns. 15,16 Although reconstructive procedures were initially considered, amputation was chosen for several reasons. First, the range of motion in the knee was markedly limited and the extensor force was basically nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…The advancement of modern treatment regimens, such as neoadjuvant and adjuvant therapy, has significantly improved overall survival rates in recent decades 6 , making long-term followup even more critical. People with rotationplasty can lead active and fulfilling lives, including participating in sports [7][8][9][10][11] . However, engaging in high-impact physical activities may increase the risk of fractures in the reoriented lower leg.…”
mentioning
confidence: 99%